1984
DOI: 10.1104/pp.76.3.599
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Inorganic Carbon Species Actively Taken Up by the Cyanobacterium Anabaena variabilis

Abstract: The nature of the inorganic carbon (C,) species actively taken up by cyanobacteria CO2 or HC03-has been investigated. The kinetics of CO2 uptake, as well as that of HC03-uptake, indicated the involvement of a saturable process. The apparent affinity of the uptake mechanism for CO2 was higher than that for HCO3-. Though the calculated V. was the same in both cases, the maximum rate of uptake actually observed was higher when HC03-was supplied. C. uptake was far more sensitive to the carbonic anhydrase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
137
2
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 12 publications
7
137
2
1
Order By: Relevance
“…To this end, several groups have reported that the CA inhibitor EZ inhibits CO2 transport in Anabaena variabilis (1,28). However, the results ofa recent study by Price and Badger (25) using Synechococcus PCC 7942 suggests that EZ, at 200 gM, equally inhibits CO2 and HCO3-transport.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…To this end, several groups have reported that the CA inhibitor EZ inhibits CO2 transport in Anabaena variabilis (1,28). However, the results ofa recent study by Price and Badger (25) using Synechococcus PCC 7942 suggests that EZ, at 200 gM, equally inhibits CO2 and HCO3-transport.…”
mentioning
confidence: 52%
“…Previous studies have suggested the participation ofa membrane-bound CA-like moiety in the transport of CO2 by Anabaena variabilis, Anacystis nidulans R2, and Synechococcus PCC 7942 (1,22,25,28). This conclusion was largely based on the observation that EZ inhibited CO2 transport (1,22,25,28) without apparent inhibition of intracellular CA (25).…”
Section: H2s Inhibition and The Mechanism Of Co2 Uptakementioning
confidence: 65%
See 3 more Smart Citations